Anti-U1-ribonucleoprotein positive and anti-Ro and anti-La negative neonatal lupus erythematosus - Angoori Gnaneshwar Rao; Vangali Srikanth Reddy; Karnam Aparna; Ruhi Haqqani; Kranthi Jagadevapuram; Sneha Gupta; Kousar Fathima; M Tejal; Divyaparimala Muppirala (Wolters Kluwer Medknow Publications, 2019)
Neonatal lupus erythematosus (LE) is associated with anti-Ro and/or anti-La antibodies. Herein, we present a 2-month-old female baby born to an LE mother in evolution. The baby was positive for U1-ribonucleoprotein antibodies and negative for anti-Ro and anti-La antibodies and was not having any systemic involvement.